EDUKASI DAN PENERAPAN TEKNIK GUIDED IMAGERY BAGI PENDERITA HIPERTENSI SEBAGAI UPAYA PENGENDALIAN TEKANAN DARAH - Febby Irianti Deski; Vania Aresti Yendrial (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2026)
Hypertension, or high blood pressure, is a global health problem that requires serious attention. It is known as the silent killer because it often presents no symptoms, causing many individuals to remain unaware of their condition until complications occur. If left uncontrolled, hypertension can lead to severe complications such as stroke, heart attack, pulmonary edema, hearing impairment, and even death. This community service program aimed to improve the ability of individuals with hypertension to control their blood pressure independently through the implementation of the guided imagery technique as a non-pharmacological intervention. The program was conducted on January 9 and 13, 2026, in the Kuranji Community Health Center (Puskesmas Kuranji) Working Area, involving 30 participants. The activities included health education on hypertension, followed by demonstration, mentoring, and hands-on practice of the guided imagery technique. Educational sessions were delivered using leaflets, a laptop, and a projector through lectures, demonstrations, discussions, and question-and-answer sessions. The program was implemented successfully and proceeded smoothly. The evaluation results showed that participant engagement reached 85%, understanding of the educational material was 80%, and participants' skills in performing the guided imagery technique reached 80%. These findings indicate that the implementation of the guided imagery technique can serve as an effective non-pharmacological approach to enhance the ability of individuals with hypertension to manage their blood pressure independently.